Selectivity of Imazapic + Imazapyr Herbicides on Irrigated Rice as Affected by Seed Treatment with Dietholate and Clomazone Applied in Preemergence - PIVETA,L.B. (2018)
ABSTRACT: The use of dietholate seed treatment, as well as the use of preemergence clomazone, can affect the selectivity of the imidazolinones chemical group of postemergence herbicides applied in crops Clearfield™. The aim was to evaluate the morphophysiological effects of a formulated mixture of imazapyr + imazapic applied in postemergence in combination with seed treatment with dietholate and applying in preemergence of clomazone on Avaxi CL rice hybrid cultivar. The experiment was conducted in the agricultural year 2012/13, in a greenhouse. The experimental design was completely randomized in a factorial design with four replications, in which factor A consisted of seed treatment with dietholate and applied clomazone herbicide in preemergence on rice and factor B consisted of eight doses of the mixture of imazapyr + imazapic herbicides. The results showed that the rice seed treatment with dietholate combined with the spray of herbicide clomazone in preemergence affects the selectivity of postemergence formulated mixture of imazapic + imazapyr applied on Avaxi CL rice. Physiological characteristics such as photosynthetic rate, transpiration rate and stomatal conductance on Avaxi CL hybrid are negatively affected.